2007
DOI: 10.1016/j.jmb.2006.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Histone Hyperacetylation in the Coding Region of Chromatin Undergoing Transcription in SV40 Minichromosomes Is a Dynamic Process Regulated Directly by the Presence of RNA Polymerase II

Abstract: SV40 chromosomes undergoing transcription operationally defined by the presence of RNA Polymerase II (RNAPII) were immune-selected with antibody to RNAPII and subjected to secondary chromatin immunoprecipitation with antibodies to hyperacetylated or unacetylated H4 or H3. Immune Selection Fragmentation and Immunoprecipitation (ISFIP) was used to determine the hyperacetylation status of histones independent of the location of the RNAPII and ReChromatin Immunoprecipitation (ReChIP) was used to determine their hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(65 citation statements)
references
References 38 publications
5
60
0
Order By: Relevance
“…Following standard PCR amplifications, amplification products were separated on 2.4% submerged agarose gels (Sigma) by electrophoresis. [12][13][14] Amplification products were visualized by staining with ethidium bromide and digitally recorded using a UVP GDS8000 gel documentation system (Ultra Violet Products).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following standard PCR amplifications, amplification products were separated on 2.4% submerged agarose gels (Sigma) by electrophoresis. [12][13][14] Amplification products were visualized by staining with ethidium bromide and digitally recorded using a UVP GDS8000 gel documentation system (Ultra Violet Products).…”
Section: Methodsmentioning
confidence: 99%
“…Simian virus 40 (SV40) is a DNA tumor virus that is organized into chromatin in the intracellular minichromosome and virion, and undergoes hyperacetylation of H3 and H4 during transcription [12][13][14] and methylation of H4K20 during an infection. 15 Because of its similarity to cellular chromatin, we hypothesized that SV40 should be able to transfer epigenetic information recapitulating the conditions of an infection to a subsequent infection through the infecting virions.…”
mentioning
confidence: 99%
“…3 Recently we have presented evidence that histones undergo sequential hyperacetylation and deacetylation during transcription. 4 Specifically we showed that in the early and late coding regions of transcribing simian virus 40 (SV40) minichromosomes immune selected with antibody to RNA polymerase II, hyperacetylated histone H4 and H3 Abbreviations used: RNAPII, RNA polymerase II; DRB, 5,6-dichloro-1-beta-D-ribobenzimidazole; HAT, histone acetyltransferase; HDAC, histone deacetylase; CTD, C-terminal domain; Cdk, cyclin-dependent kinase; ISF, immune selection and fragmentation; Re-ChIP, re-chromatin immunoprecipitation; ISFIP, ISF followed by a second immunoprecipitation; siRNA, small interfering RNA; GAPDH, glyceraldehyde-3-phosphate dehydrogenase; VP1, viral protein 1.…”
Section: Introductionmentioning
confidence: 99%
“…4 Two aspects of this model which were not explored extensively in our publication 4 were the relationship between histone deacetylation and translocation by the RNAPII complex and whether p300 was required for histone hyperacetylation and transcription. In order to address these issues we now report on the effects of RNAPII translocation inhibitors and a small interfering RNA (siRNA) to p300 on the SV40 transcription process.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies with SV40 have revealed a dynamic state of the viral minichromosome during replication. Extensive remodeling of viral chromatin occurs during replication in terms of the distribution and state of acetylation of nucleosomes, coinciding with the early versus late phases of viral gene expression and distribution of RNA polymerase II (2).…”
mentioning
confidence: 99%